2020
DOI: 10.3892/or.2020.7487
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‑related apoptosis‑inducing ligand as a therapeutic option in urothelial cancer cells with acquired resistance against first‑line chemotherapy

Abstract: Patients with urothelial carcinoma frequently fail to respond to first-line chemotherapy using cisplatin and gemcitabine due to development of resistant tumor cells. The aim of the present study was to investigate whether an alternative treatment with tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) that induces tumor cell death via the extrinsic apoptotic pathway may be effective against chemotherapy-resistant urothelial cancer cell lines. The viability of the urothelial cancer cell line RT112 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The TRAIL apoptosis induction system has attracted the attention of researchers since its discovery because of its ability to trigger apoptosis primarily in tumor cells [8,17,20]. Although TRAIL can interact with several different receptors, only DR4 and DR5 contain the intracellular death domain necessary for apoptotic signal transmission after ligand binding to the receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRAIL apoptosis induction system has attracted the attention of researchers since its discovery because of its ability to trigger apoptosis primarily in tumor cells [8,17,20]. Although TRAIL can interact with several different receptors, only DR4 and DR5 contain the intracellular death domain necessary for apoptotic signal transmission after ligand binding to the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of FAS expression was found to significantly correlate with worse prognosis in patients with urothelial carcinomas of the bladder, ureter, and renal pelvis [16]. Apparently, proper identification and clarification of the exact apoptotic machinery and pathways in different tumor cell types may ameliorate the design of more efficacious targeted cancer treatments [1,3,17].…”
Section: Introductionmentioning
confidence: 99%
“…Combination treatment with TRAIL and the SMAC mimetic LCL-161 resulted in an increased cytotoxicity compared to monotherapies. Whereas enhanced expression of cIAP1/2 and XIAP was noted after TRAIL treatment, presumably as a response to the pro-apoptotic stimulus, a reduced expression was after combination treatment with TRAIL and LCL-161 (41). In a recent study, the SMAC mimetic ASTX660, also known as Tolinapant, was found to induce necroptosis in apoptosisinsensitive BC cells by turning TNF-a into a cytotoxic signal (42).…”
Section: Targeting Ciap1/2 and Xiap In Bcmentioning
confidence: 99%
“…DEBIO-1143 treatment reversed carboplatin-resistance of ovarian cancer cells by inducing apoptotic or necroptotic cell deaths (96). Similarly, first line chemotherapy-resistant urothelial cancer cells well responded to TRAIL after SMAC mimetic treatment (97).…”
Section: Targeting the Inhibitors Of Apoptosismentioning
confidence: 99%